Clean air suits vs scrub suits: what are the benefits of using them for infection control in hospitals? - Abreu, Maria José (2014)
Experts in infection control are often asked about issues related to the use of scrubs and clean air suits in the operating room (OR). So far there is no clear explanation or mandatory obligation why the surgical team has to wear clean air suits or scrub suits in the operating rooms (OR´s) and more importantly, what are the main differences between these two type of clothing. There is a general perception that the two are equal or very similar. So, what are clean air suits and scrub suits? Where did the concept and employ originate? Are they necessary from an infection control point of view, are they an useful resources of preventing or controlling transmission of infection?